Health‐care professionals' assessment of a person‐centred intervention to empower self‐management and health across chronic illness: Qualitative findings from a process evaluation study - Kristin Heggdal; Joshua B. Mendelsohn; Natalie Stepanian; Bjørg Frøysland Oftedal; Marie Hamilton Larsen (Wiley, 2021)
Abstract Background Person‐centred care (PCC) empowers patients to manage their chronic illness and promote their health in accordance with their own beliefs, values and preferences. Drawing on health‐care professional's (HCP's) experiences implementing an empowerment‐focused, person‐centred intervention called the Bodyknowledging Program (BKP), we undertook a process evaluation that aimed to assess the impact on patient health and well‐being. Methods We used individual in‐depth interviews and semi‐structured focus groups comprising n = 8 interprofessional HCP who facilitated intervention sessions with n = 58 patients situated in Norwegian specialist care sites. Content analysis was used to analyse the data and summarize major themes. Results Health‐care professional interviews revealed four main ways in which the intervention operated in support of health‐related patient outcomes: (i) addressing the whole person; (ii) hope and affirmation; (iii) expanding recovery; and (iv) social support and revitalized relationships. The intervention provided new tools for patients to understand the social, emotional and physical impact of their illness. Health‐care professional reported new insights to facilitate patient engagement and to promote patients' health. Conclusions The Bodyknowledging Program facilitated patient engagement through the promotion of patient‐centred care while developing the patients' ability to exploit their own resources for effectively managing their health within illness. The process evaluation supported the underlying theoretical basis of the intervention and was suggestive of its potential transferability elsewhere.